1990
DOI: 10.1002/pola.1990.080281117
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a thermally imidized soluble polyimide film

Abstract: A soluble aromatic poly (amic acid) film was converted to a soluble polyimide by staging at 25°C intervals to 325°C and characterized at each interval by several analytical methods. The behavior observed was consistent with an interpretation that a reduction occurred in molecular weight of the poly (amic acid) during the initial stages of cure before the ultimate molecular weight was achieved as a polyimide. This interpretation was supported by the results of solution viscosity, gel permeation chromatography, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 29 publications
2
25
0
Order By: Relevance
“…-+ + + + + + + + + + + + UDABDA2 -+ + + + + + + + + + + + UDABDA3 -+ + + + + + + + + + + + BPFBPA -+ + -+ -+ + + + + + BPClHPB -+ + -+ + + + + + + + BPFHDMPB -+ + + -+ -+ + + + + + a Solubility, + +1 soluble at room temperature, + -, partially soluble on heating at 70 of 4 inh between the poly(amic acid) and its polyimide, as observed here with UDABDA3 and with some samples of UDABDA2, was also reported by Young et al [10] in their thorough study of imidization as a function of the degree of thermal curing of a poly(amic acid). These investigators found a significant decrease in molecular weight with initial curing followed by an increase in the later stages so that the fully imidized material had approximately the molecular weight of its precursor poly(amic acid).…”
Section: Characterization Of Polyimides and Poly(arylene Ethers)supporting
confidence: 85%
“…-+ + + + + + + + + + + + UDABDA2 -+ + + + + + + + + + + + UDABDA3 -+ + + + + + + + + + + + BPFBPA -+ + -+ -+ + + + + + BPClHPB -+ + -+ + + + + + + + BPFHDMPB -+ + + -+ -+ + + + + + a Solubility, + +1 soluble at room temperature, + -, partially soluble on heating at 70 of 4 inh between the poly(amic acid) and its polyimide, as observed here with UDABDA3 and with some samples of UDABDA2, was also reported by Young et al [10] in their thorough study of imidization as a function of the degree of thermal curing of a poly(amic acid). These investigators found a significant decrease in molecular weight with initial curing followed by an increase in the later stages so that the fully imidized material had approximately the molecular weight of its precursor poly(amic acid).…”
Section: Characterization Of Polyimides and Poly(arylene Ethers)supporting
confidence: 85%
“…This effect has been monitored by, for example, Laius et al [47] on insoluble PI, both by changes in mechanical properties during imidisation and by spectroscopic studies from the temporary appearance of an anhydride carbonyl absorption band between 100 and 250 8C. Evidence of this effect was later verified by Young et al, [48] measuring the molecular weight of the PI at different stages of thermal imidisation. The molecular weight gradually regained at high temperature.…”
Section: Thermal Cyclisationmentioning
confidence: 69%
“…However, the PI films obtained were somewhat brittle in many cases. This is probably due to partial retropolyaddition although the generated terminal functional groups can recombine by additional heating at higher temperatures [33]. Then, to obtain flexible PI films while avoiding film coloration, thermal imidization was carried out typically at 200 C/ 20min þ 250 C/30min þ 320 (or 300) C/1 h in vacuum as adhered on the substrate, and successively annealed in vacuum at 10e20 C lower temperatures than the T g 's after peeling them off from the substrate to eliminate residual stress without undesirable significant film deformation.…”
Section: Monomermentioning
confidence: 97%